Efficacy of citronella and ginger essential oil combinations against chicken lice (Menopon gallinae) and mites (Ornithonyssus bursa): Chemical characterization, contact toxicity, and in vivo validation - Nattha Vigad; Prapakorn Tarachai; Sunee Chansakaow; Veerasak Punyapornwithaya; Kridda Chukiatsiri (Veterinary World)
Background and Aim: Ectoparasites, such as Menopon gallinae (chicken lice) and Ornithonyssus bursa (chicken mites), have a significant impact on poultry health and productivity, resulting in substantial economic losses and potential zoonotic risks. Conventional synthetic pesticides, though effective, pose health and environmental concerns. Hence, plant-based alternatives such as essential oils are gaining attention for their insecticidal properties. This study aimed to characterize the physical and chemical properties of citronella (Cymbopogon nardus) and ginger (Zingiber officinale) essential oils and to evaluate their acaricidal and insecticidal efficacy, both in vitro and in vivo, against M. gallinae and O. bursa.